2012
DOI: 10.2478/v10213-012-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Adenovirus Field Strains in Birds Infected with Marek’S Disease Virus

Abstract: The strains of adenoviruses were isolated from 356 birds with clinical form of Marek's disease and coinfection with adenoviruses. A hexon gene fragment coding loop L1 of adenovirus strains was sequenced and obtained data were analysed with BLAST, Geneious 5.3, and MEGA5 software by comparison with nucleotide sequences of reference strains of fowl adenoviruses (FAdV-1 -FadV-12), two turkey adenoviruses, and two goose adenovirus strains. On this basis, serotypes of adenovirus strains were determined. Sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These are further classified into 12 serotypes, 1-8a, 8b-11, of which some members are associated to certain diseases. Although implicated, the pathogenicity of most AAV, particularly FAdVs, is not well defined ( Niczyporuk et al., 2012 ). Some strains may act as primary or secondary pathogens ( Toro et al., 2000 , Niczyporuk et al., 2012 , Niczyporuk et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are further classified into 12 serotypes, 1-8a, 8b-11, of which some members are associated to certain diseases. Although implicated, the pathogenicity of most AAV, particularly FAdVs, is not well defined ( Niczyporuk et al., 2012 ). Some strains may act as primary or secondary pathogens ( Toro et al., 2000 , Niczyporuk et al., 2012 , Niczyporuk et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although implicated, the pathogenicity of most AAV, particularly FAdVs, is not well defined ( Niczyporuk et al., 2012 ). Some strains may act as primary or secondary pathogens ( Toro et al., 2000 , Niczyporuk et al., 2012 , Niczyporuk et al., 2013 ). However, under certain conditions, such as inclusion body hepatitis ( IBH ) and hydropericardium hepatitis syndrome ( HPS ), FAdVs have been directly involved, wherein disease has been replicated using field isolates ( Okuda et al., 2006 , Mase et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive agents, such as infectious bursal disease virus (IBDV), chicken infectious anaemia virus (CIAV), and Marek's disease virus (MDV) (20,21) are predisposing factors to IBH outbreaks or can exacerbate clinical manifestations concurrently with FAdV infections (16). Studies in Canada, the United States, and New Zealand indicated that IBH occurred as a primary disease, without association with IBDV or CIAV (4,23).…”
Section: Discussionmentioning
confidence: 99%
“…In poultry farms, viral coinfections are becoming increasingly frequent. Adenovirus infections are often described as coinfections involving viruses such as infectious bursal disease virus (IBDV) [ 1 ], avian reoviruses (ARVs) [ 2 ], Marek’s disease virus (MDV) [ 3 , 4 ], and chicken infectious anaemia virus (CIAV) [ 1 , 5 7 ]. Fowl adenoviruses (FAdVs) are double-stranded DNA viruses of the adenovirus genus of the Adenoviridae family.…”
Section: Introductionmentioning
confidence: 99%